2019
DOI: 10.1007/s12237-019-00530-4
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variation in Food Web Structure and Fish Community Composition in the East/Japan Sea

Abstract: The aim of this study was to assess the temporal variability in the trophic structure of a fish community and the trophic levels of dominant fish species off the eastern coast of Korea. We analyzed the community composition and the stable carbon and nitrogen isotope ratios (δ 13 C and δ 15 N) for fish species in Hupo coastal waters over four seasons. Fish assemblages were mainly dominated by resident benthic and benthopelagic fish. In contrast, there were low numbers of pelagic fish, including migrating and oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 88 publications
8
19
0
Order By: Relevance
“…Based on the δ 15 N values of herbivores and suspension feeders as benthic and pelagic baselines, respectively, and assuming a trophic fractionation of 3.3 ± 0.26 (McCutchan et al, 2003), our TL estimation denoted that the marine ranching ecosystem is characterized by a trophic length of 3.5, as observed previously in the adjacent restored macroalgal bed (Kang et al, 2008) and natural rocky habitat (Park et al, 2020). The gap in δ 15 N values between primary (herbivores) and tertiary (predatory fish) consumers recorded on average 2.6 to 4.6 (MH site) and 1.8 to 4.6 (PH sie).…”
Section: Food Web Structure Of Marine Ranching Ecosystemmentioning
confidence: 64%
See 1 more Smart Citation
“…Based on the δ 15 N values of herbivores and suspension feeders as benthic and pelagic baselines, respectively, and assuming a trophic fractionation of 3.3 ± 0.26 (McCutchan et al, 2003), our TL estimation denoted that the marine ranching ecosystem is characterized by a trophic length of 3.5, as observed previously in the adjacent restored macroalgal bed (Kang et al, 2008) and natural rocky habitat (Park et al, 2020). The gap in δ 15 N values between primary (herbivores) and tertiary (predatory fish) consumers recorded on average 2.6 to 4.6 (MH site) and 1.8 to 4.6 (PH sie).…”
Section: Food Web Structure Of Marine Ranching Ecosystemmentioning
confidence: 64%
“…Alternatively, carbon and nitrogen stable isotope analyses (referred to here as δ 13 C and δ 15 N values, respectively) have been applied successfully to the identification of diets, feeding habits, and trophic ecology of cephalopods (Cherel et al, 2009;Merten et al, 2017;Murphy et al, 2020). The dietary resources of a species within a marine food web can be resolved by the δ 13 C values of its tissues, as the latter contains information on the source (benthic or pelagic) of prey items (Kang et al, 2008;Park et al, 2020). Similary, their δ 15 N values provide an estimation of their position in the food web, increasing with the assimilation of resources at relatively higher trophic levels (TLs; Post, 2002;Caut et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Scientists have realized the importance of deeply capturing the relationship between marine communities and seasonal changes of ocean warming at a finer scale (considering season or shorter time periods). Some studies have also presented apparent seasonal fluctuations of fish abundance and biodiversity in marine ecosystems by assessing and understanding the composition and seasonal changes of the fish assemblage and doing relevant statistical analyses [ 14 – 17 ]. The results suggested that these seasonal variations could derive from the migration and arrival of species and their own seasonal changes of behavior related to the seasonality of temperature patterns.…”
Section: Introductionmentioning
confidence: 99%
“…Scientists have realized the importance of deeply capturing the relationship between marine communities and seasonal changes of ocean warming at a finer scale (considering season or shorter time periods). Some studies have also presented apparent seasonal fluctuations of fish abundance and biodiversity in marine ecosystems by assessing and understanding the composition and seasonal changes of the fish assemblage and doing relevant statistical analyses [3, 30, 50, 72]. The results suggested that these seasonal variations could derive from the migration and arrival of species and their own seasonal changes of behavior related to the seasonality of temperature patterns.…”
Section: Introductionmentioning
confidence: 99%